RETRACTED ARTICLE: Analysis of Influence Factors of Marine Fishery Industry Structure Optimization on Carbon Emission Efficiency Based on Depth Feedforward Model - Dayong Chen (Journal of Experimental Nanoscience)
We, the Editor and Publisher of the Journal of Experimental Nanoscience, have retracted the following article, which is part of the Special Issue titled Adaptive Nanotechnology for Environmental Sustainability:Dayong Chen (2023) analysis of influence factors of marine fishery industry structure optimization on carbon emission efficiency based on depth feedforward model, Journal of Experimental Nanoscience, 18:1, DOI: 10.1080/17458080.2023.2174696Following publication, concerns were raised about the peer review and decision-making processes for this special issue.After an investigation by the Taylor & Francis Publishing Ethics & Integrity team, in full cooperation with the Editor-in-Chief, it was confirmed that the article was not reviewed appropriately, in line with the Journal’s peer review standards and policy.As the stringency of the peer review process is core to the integrity of the publication process, the Editor and Publisher have decided to retract the article. The authors have been informed of this decision.We have been informed in our decision-making by our editorial policies and the COPE guidelines.The retracted articles will remain online to maintain the scholarly record, but they will be digitally watermarked on each page as ‘Retracted’.